Spacetime Metamaterials-Part I: General Concepts - Caloz, Christophe; Deck-Leger, Zoe-Lise (IEEE transactions on antennas and propagation, 2020)
This article deals with the general concepts underpinning spacetime metamaterials and related systems. It first introduces spacetime metamaterials as a generalization of (bianisotropic) metamaterials, presented in the holistic perspective of direct and inverse spacetime scattering, where spacetime variance and dispersion offer unprecedented medium diversity despite some limitations related to the uncertainty principle. Then, it describes the fundamental physical phenomena occurring in spacetime systems, such as frequency transitions, nonreciprocity, Fizeau dragging, bianisotropy transformation, and superluminality, allowed when the medium moves perpendicularly to the direction of the wave. Next, it extends some principles and tools of relativity physics, particularly a medium-extended version of the spacetime (or Minkowski) diagrams, elaborates a general strategy to compute the fields scattered by spacetime media, and presents a gallery of possible spacetime media, including the spacetime step discontinuity, which constitutes the building brick of any spacetime metamaterial. Finally, the conclusion section provides a list of 16 items that concisely summarizes the key results and teachings of the overall document. The second part establishes the theory and overviews some current and potential applications of spacetime metamaterials.